Ugric vocabulary (appendix to Grünthal et al. 2022: Drastic demographic events triggered the Uralic spread) - Holopainen, Sampsa (Zenodo, 2022)
Ugric cognates (Appendix to the paper Grünthal, R., Heyd, V., Holopainen, S., Janhunen, J., Khanina, O., Miestamo, M., Nichols, J., Saarikivi, J. & Sinnemäki, K. 2022: Drastic demographic events triggered the Uralic spread. – Diachronica. https://doi.org/10.1075/dia.20038.gru) Words found only in Hungarian and Khanty and/or Mansi. Further work on Ugric etymologies (with updates to the information on this table) will be published on https://sanat.csc.fi/wiki/Hungarian_Historical_Phonology : Part of this work has been done by the author as a fellowship holder of the Austrian Academy of Sciences (APART-GSK) at the Finno-Ugrian department of the University of Vienna.